Gen X-Gen Z: communication and education in the Pancasila values campaign - Rohid, Nibrosu; Rohid, Nabrisi; Sukisno, Sukisno; Surya, Andi; Khang, Nguyen Tan (Jurnal Studi Komunikasi, 2026)
This research analysed the hybrid forms of communication between Generation X and Generation Z in campaigns promoting adherence to Pancasila values within student organisations, as well as their implications for the process of re-actualising national ideology in the digital era. This study employed a descriptive qualitative approach and was conducted in Tuban Regency, East Java. Data were obtained through semi-structured interviews with six faculty advisers (Generation X) and six student organisation leaders (Generation Z), as well as through participant observation and digital documentation of face-to-face forums and organisational social media. Data analysis was carried out inductively and thematically using the Miles, Huberman, and Saldaña model. The findings indicate that intergenerational communication occurs through a hybrid communication pattern that combines offline reflective forums with online collaborative activities. Generation X serves as the guardian of the legitimacy of Pancasila values and their moral depth, while Generation Z functions as the translator of these values into digital expressions and social action. Despite perceptual tensions regarding the ways in which ideological values are conveyed, the interaction between the two groups resulted in a convergence of meaning that enriched the process of value internalisation. The digital campaign themed Pancasila and Environmental Sustainability showed an increase in student participation of up to 64% and a digital engagement rate of 8.7%, indicating the success of an adaptive and collaborative communication model. Theoretically, this research expands the application of intergenerational communication theory in the context of ideological education. Socially, the hybrid communication model has proven capable of strengthening the national identity of the younger generation by presenting Pancasila as a dynamic, reflective, and relevant life narrative in the digital age.